Viruses of Entamoeba histolytica I. Identification of Transmissible Virus-Like Agents - Diamond, Louis S. (1972)
This and a companion report deal with the identification and morphogenesis of viruses in axenized cultures of Entamoeba histolytica. There are probably two different types of virus each producing a different pathological picture in different amoebal strains, or, less likely, there is one type of agent having widely different morphological and morphogenetical pictures in different strains of E. histolytica. Both types of agent produce a lytic response in axenized amoebae and have been serially passaged to an extent assuring their replicating nature. One appears to replicate in the nucleus as multiple clusters of fine filaments which ultimately lyse the nucleus, causing cell death. The second type of agent appears to be a typical polyhedral virus, seen only in the cytoplasm and also resulting in lysis of the cell. A particle morphologically indistinguishable from this second agent is also found in late passages of the agent producing the nuclear pathology.